Genetic diversity of some Ghanaian pigs based on microsatellite markers - Ayizanga, R.A.; Kayang, B.B.; Adomako, K.; Adenyo, C.; Inoue-Murayama, M.; Asamoah, L. (2016)
A knowledge of the level of genetic diversity is very important in ensuring the sustainable utilisation of animal genetic resources. To this end, the genetic diversity of some local pigswas assessed by genotyping 86 unrelated pigs in four regions of Ghana namely Northern (Tingoli = 9), Upper West (Papu = 31 and Babile = 32) and Upper East (Gia = 14) using 12 microsatellite markers.The number of alleles (Na), number of effective alleles (Ne), observed heterozygosity (Ho), expected heterozygosity (He) and inbreeding coefficient (FIS) were used to assess the level of genetic differentiation among the five populations in this study. All loci studied were polymorphic and the mean number of alleles ranged from 4.58 (Yorkshire) to 10.58 (Papu) with an overall average of 7.65 alleles. At all the 12 loci studied, inbreeding coefficient (FIS) deviated significantly from zero with a mean of 0.32. When the Nei’s standard genetic distance based on the proportions of shared alleles was used to construct a neighbour joining tree, pigs from the different communities sampled in the Upper West region emerged with the highest bootstrap value of 90%. Generally, the sampled pigs represent distinct populations with a moderate amount (12%) of genetic differentiation but considerable amount of inbreeding (29%) has taken place within these populations over the years. This is the first report of the genetic diversity of Ghanaian local pigs using microsatellite markers.